VALUE HARMONISATION COSMOPOLITAN & NATIONALISM THROUGH CIVIC EDUCATIONFOR LOCAL CHARACTER EDUCATION GLOBAL PERSPECTIVE - KARIADI, DODIK (Universitas Muhammadiyah Ponorogo, 2017)
This article is the result of a study on the harmonization of cosmopolitan values and nationalism in teaching civics as well as how these two ideas could create educational output that has global knowledge but do not forget a good personality or character that has been planted since the beginning. The study was motivated by the severe problems of the national consciousness (national consciousness) young people today who need serious revamping. In the era of globalization, the Indonesian people are faced with two major forces that are in tandem with globalization cosmopolitanism and nationalism with a marked weakening of the emergence of ideas of regionalism, broad autonomy, separatism and racial conflicts. Based on this, the study of how the process of harmonization of cosmopolitan values and nationalism in teaching civics and how the ideas can be a way for the creation of a sound education global output but remain local in character. Despite the fact that conceptually there is a contradiction between the cosmopolitan values of nationalism, both are at the poles of attraction, where the value of cosmopolitan pulled into the global sphere, while the value of nationalism pulled into the exclusive domain. In such a situation Civics learning is expected to be a bridge to harmonize both values. Value cosmopolitan and nationalism became the crucial factor in developing a global perspective but does not eliminate local character when done through learning Civics quality, quality and meaningful.